IMPLEMENTASI ZAKAT TERHADAP PERTUMBUHAN EKONOMI DILIHAT DARI PERSPEKTIF EKONOMI ISLAM - Amelia Amelia; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
Zakat has become a source of state financial income that has a very important role, among others, as a means of developing Islam, providing assistance services for the benefit of the social welfare of the underprivileged such as the poor, as well as other assistance. One of the roles that zakat has is its role in reducing the poverty rate of society. This study aims to find out how the implementation of productive zakat plays a role in economic growth. To increase the economic growth of the community, what the BAZNAS institution must do is emphasize the function of productive zakat. The research method used in this research is qualitative with a descriptive approach. The data collection techniques use library techniques or library research. The inhibiting factors in the implementation of zakat to help increase economic growth are caused by several factors, namely, knowledge about the terms of consumptive zakat and productive zakat has not been properly socialized, and the lack of trust of muzakki to zakat amil in zakat management